CONCERNING NOISE IN ELECTRONIC AND COMMUNICATIONS SYSTEMS - González Ríos, Jorge Luis (Telemática, 2020)
Noise is inherent to all electronic and communication systems, a fact that must be taken into account and its consequences on the system studied or designed must be analyzed. It can be defined simply (but categorically) as any random interference not related to the signal of interest and limits the minimum signal level that can be processed by a circuit or system with acceptable quality. In this paper, some basic concepts about noise and its modeling in two-port networks will be reviewed, the obtaining of noise parameters in a specific circuit will be exemplified and some lines of research currently being developed in this topic will be cited.